Prototyping: a pedagogical approach to complex realities from the field of design (2023)
The objective of this article is to analyze a creation-research experience in education from the field of design focused on the question: how to generate pedagogical experiences that bring us closer to complex realities? The “Context and Region course: Introduction to Systemic Thinking” taught at Universidad de Ibagué (Colombia) was taken as a case study. This subject is taught under a line of design work where a teaching-learning methodology was structured in four moments: comprehension, intuitive stage development, approach to contexts and complex realities from the simulation, and design of collective actions. The results of this analysis ended up in categories such as "prototyping", an emerging concept close to design that articulated ideation with the feel-think - an action contrary to the drastic separation between feelings and rational thought - from a constant creative tension of students and teachers. This undoubtedly led to mobilizing these actors outside their comfort zones, identifying and questioning prejudices and subjective convictions, but also turning it into a transversal exercise of complete relevance in the professional training of students from different disciplines by promoting the dialogue of knowledge to favor increasingly broad senses of the human nature. Finally, the understanding of what has been called "complex realities" in systemic and complexity theories was approached from processes of observation and educational reflection, understanding design not only in its pragmatic-objective function, but also as a social praxis.